IMPLEMENTASI SUPERVISI MANAJERIAL PENGAWAS SEKOLAH DALAM MENINGKATKAN KOMPETENSI PENGELOLA PERPUSTAKAAN - Resi Yulia Wulandari (Manajer Pendididikan, 2016)
The objective of this study was to evaluate the role of managerial supervision supervisors to improve the competence of the library manager Senior High School 6 Seluma accordance with specified standards. The method in this research is evaluative. The result of this research Showed the role of managerial supervision appropriate supervisory standards in the planning and reporting of managerial supervision supervisors to increase the competence of library managers in Senior High School 6 Seluma, whereas for the implementation of managerial oversight supervision is still in fairly standard criteria.Keywords: implementation, supervision managerial supervision, library officer.